Analisis Risiko Usahatani Melon Minion (Cucumis melo L.) Hidroponik di PT Benih Sumber Andalan Kabupaten Bogor Provinsi Jawa Barat - ANDREA, TRISHA SUSANA; SUKENDAR, NI MADE CLASSIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Risk Analysis of Hydroponic Minion Melon (Cucumis melo L.) Farming at PT Benih Sumber Andalan, Bogor Regency, West Java Province.  Melon minion (Cucumis melo L.) is a development of melon plant breeding in Indonesia, especially to produce local cultivars that are superior and have sales value in the community. The advantages of this melon include its small shape, very sweet taste, and high economic value, making it suitable for development for local consumption. This research aims to identify risks, measure the level of production risk using the FMEA (Failure Mode and Effect Analysis) method, and map the mitigation steps taken to minimize risk events in the hydroponic minion melon farming at PT Benih Sumber Andalan. The research results showed that there were 11 risk events found in the division of activities starting from planning, planting, maintenance, to distribution. The highest risk is in the intolerable category with an RPN value of 48, and the lowest risk is in the Broadly Acceptable category with an RPN value of 3. A mitigation plan has been formulated regarding the causes of risks in the supply chain, some of which are: (1) Using fans/blowers, (2) Adjusting watering volume, (3) Tightening routine supervision and back up, (4) Carrying out joint evaluations, and (5) Implementing a reward and punishment system for workers.